The Risk Factors of Alcohol Dependence Severity Due to the Pandemic: A Bayesian Approach - Selahattin Caner; Nihan Potas; Nilüfer Koçtürk (Addicta: The Turkish Journal on Addictions)
During pandemic periods, people are at risk not only in terms of health but also in terms of alcohol addic- tion. Within the scope of this study, determining the existence of a tendency toward alcohol dependence in individuals during and after the pandemic is aimed. The study sample consists of 1068 participants aged 20+ living in Türkiye. In this study, in which the quantitative approach was used, the risk factors and causes (participants characteristics, coronavirus disease 2019 Anxiety Scale, alcohol use, and coping with the pandemic) of alcohol dependence severity were examined. The classical and Bayesian estimation meth- ods in linear regression were used. According to Bayesian estimation, the variables affecting the severity of alcohol dependence were found to be “gender + employment status + working hours + loss of a relative due to pandemic disease + pre-pandemic alcohol consumption + coronavirus disease 2019 Anxiety Scale + cogni- tive coping + behavioral coping + alcohol use disorder.” In conclusion, we should develop a total struggle in medical, psychological, and social fields to protect public health, revise existing alcohol addiction education programs specific to the pandemic and identify risk groups in terms of determined variables. Providing ser- vices to these individuals with priority may help reduce alcohol addiction.